The Influence of Solvent Concentration and Long Soaking to Quality Gelatin Fish Scales Red Snapper (Lutjanus camphecanus Sp.) - Eka Triastuti, Warlinda; Agustiani, Elly; Surono, Agus; Dwi Cahyasani, Rensi; ., Avidata (Journal of Food Security and Agriculture; Vol 1 No 2 (2017): Journal of Food Security and Agriculture, 2017)
Gelatin have been successfully isolated from skin of brownstripe red snapper (Lutjanus campechanus sp.) by citric acid immersion and hydrolysis process. Variation of citric acid are 1%, 3%, and 5% (%v/v) for 1,2,3,4 and 5 days. Gelatin was analyzed Fourier transform infrared spectroscopy (FTIR); proximate analysis which includes yield and moisture content; analysis of physical properties - chemical include viscosity and acidity (pH); Organoleptic test (Color, smell, and taste). FTIR spectroscopy was conducted on gelatin from skin of brown stripe red snapper with citric acid immersion. FTIR analysis of gelatin shows O-H, C-H, C=O, N-H dan C-C aromatic groups which are exactly same with that the comercial gelatin. The best results obtained in the immersion gelatin with 1% citric acid with gelatin viscosity from 1.82 to 2.22 cp, gelatin moisture content of 13.6 -33.7%, and pH of gelatin about 6.32 to 6.82.